The Concept of Love in Islamic Thought: Between Spirituality and Human Relations - Suud Sarim Karimullah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
This study explores the concept of love in Islam, emphasizes its spiritual dimension, and relates it to a broader impact on human life. With an in-depth analysis of relevant literary sources, it was found that love in Islamic thought is not only concerned with the relationship with Allah but also includes how love affects social interactions and relationships between people. This concept of love carries a deep spiritual dimension and inspires living life. Philosophical and theological approaches affirm the essential role of love in giving meaning to life, with deep ethical consequences. The harmony between the spiritual and social dimensions of love produces positive impacts in various aspects of life, including interreligious relations, social services, education, and many other areas. Through this understanding, individuals and communities are directed to live life with deep love, which connects spirituality with social responsibility, forms ethical and caring individuals, and contributes to creating a better world.